2013
DOI: 10.1007/s12185-013-1319-7
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome in a child with EBV-negative aggressive NK cell leukemia

Abstract: Aggressive natural killer cell leukemia (ANKL) is a rare malignant disorder of mature NK cells frequently associated with Epstein-Barr virus (EBV). This malignancy is typically treated with intensive remission induction chemotherapy followed by allogeneic hematopoietic stem cell transplantation (HSCT). EBV-negative ANKL and childhood ANKL, however, are not well defined and the optimal therapeutic strategy in these cases is poorly understood. Here, we present a unique pediatric EBV-negative ANKL patient who ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The following antibodies were used to access T and NK cells: CD3 PerCP-Cy5. 5 13 The bioinformatics pipeline produces a list of annotated variants that have a depth of read of at least × 50 (with Phred quality score 430). This pipeline filters out: all variants with frequency 41% reported in 1000Genome, exAC (The Exome Aggregation Consortium), and ESP (Exome Sequencing Project) databases; any variants that are in the UTR or upstream/downstream of the gene; variants with a synonymous coding effect and variants within intronic region, unless they result in splice site mutations.…”
Section: Flow Cytometric Immunophenotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…The following antibodies were used to access T and NK cells: CD3 PerCP-Cy5. 5 13 The bioinformatics pipeline produces a list of annotated variants that have a depth of read of at least × 50 (with Phred quality score 430). This pipeline filters out: all variants with frequency 41% reported in 1000Genome, exAC (The Exome Aggregation Consortium), and ESP (Exome Sequencing Project) databases; any variants that are in the UTR or upstream/downstream of the gene; variants with a synonymous coding effect and variants within intronic region, unless they result in splice site mutations.…”
Section: Flow Cytometric Immunophenotypingmentioning
confidence: 99%
“…To the best of our knowledge, there have been 16 cases reported in the English literature, [2][3][4][5][6][7][8][9] often as single case reports or rare exceptions included in the studies of EBVpositive aggressive NK-cell leukemia/lymphoma. [2][3][4][5][6][7][8] A recent study of a series of seven cases has shown that the EBV-negative aggressive NK-cell leukemia/ lymphoma is indistinguishable clinically and pathologically from EBV-positive counterpart, 9 in contrast to some earlier reports suggesting that patients with EBV-negative aggressive NK-cell leukemia/lymphoma have a less aggressive clinical course and more favorable response to treatment. 2,5,7 Most of the studies on the pathogenesis of NK/ T-cell lymphomas were on extranodal NK/T-cell lymphoma, nasal type, or its cell line derivative, with very limited information on aggressive NK-cell leukemia/lymphoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since its description by Fernandez et al in 1986 14 , sporadic EBV negative ANKL cases have been reported . EBV-negativity has been speculated to correlate with a less aggressive clinical outcome 15,11 . However, the rarity of the reported cases precludes firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, occasional reports of EBV-negative ANKL have been described 1, 5, 6, 911 and a slightly better outcome observed was attributed to an EBV-negative status 6, 11 . Nevertheless, the limited number of the cases reported hampers definitive conclusions.…”
Section: Introductionmentioning
confidence: 91%